ASPEK-ASPEK TINDAK PIDANA DALAM PERBANKAN SYARIAH DAN KONVENSIONAL - Hamsir Hamsir (El-Iqthisadi, 2020)
AbstractThe purpose of this paper is to observe, predict and assess the existence of Islamic banking in Indonesia in the development of facing and maintaining public confidence in the issue of banking crime that are currently, have been and will come. Sharia Bank As an institution in the form of a business / service industry, so in the future, commercial/state banks such as state-owned enterprise banks that manage Sharia Banks will be merged as separate National Sharia Banks. Space and opportunities for criminal acts in Islamic banking have the same space and opportunities as other banks (conventional banking). However, what distinguishes if a criminal act is suspected, it must involve institutions formed from the provisions in sharia banking law (national sharia board, sharia supervisory board) accompanied by the Police and financial service authority institutions, but in investigative work. The police apparatus or financial services authority first asks for instructions from the national sharia board and sharia supervisory board.Keywords: Crime, Conventional Banking, Sharia Banking. AbstrakTujuan penulisan ini, untuk mengamati, memprediksi dan menilai keberadaan perbankan syariah di Indonesia dalam perkembangan menghadapi dan menjaga kepercayaan masyarakat dari persoalan tindak pidana perbankan atau kejahatan perbankan yang saat ini, pernah dan atau akan datang.  Bank (Syariah) Sebagai suatu institusi/lembaga dalam bentuk usaha/industri jasa (BUMN), begitu pun ke depan (wacana 2020) Bank-bank umum/negeri (BNI, BRI & Mandiri) yang mengelola Bank Syariah akan dimerger sebagai Bank Syariah Nasional tersendiri. Ruang dan peluang terjadinya tindak pada perbankan syariah memiliki ruang dan peluang yang sama dengan perbankan lainnya (konvensional). Namun yang membedakan bila diduga terjadi tindak pidana di dalamnya, haruslah melibatkan lembaga-lembaga yang terbentuk dari ketentuan dalam hukum/perundang-undangan perbankan syariah (DSN, DPS) disertai institusi Kepolisian dan lembaga OJK, namun dalam kerja penyidikan aparat Polri atau OJK terlebih dahulu meminta petunjuk DSN dan DPS.Kata Kunci : Perbankan Konvensional, Perbankan Syariah, Tindak Pidana.